Penggunaan Metode Speed Reading untuk Meningkatkan Kemampuan Membaca Siswa SD Islam Miftahus Shibyan Kecamatan Plosoklaten Kediri - Triska Devi Dela Vania; Miftahudin (Universitas Islam Tribakti Lirboyo Kediri, 2020)
The purpose of this study was to determine the success of improving the reading skills of Islamic Elementary School students Miftahus Shibyan using the speed reading method. This research uses descriptive qualitative research. The subjects of this study were the Principal, Educators and Education Personnel, and Students. The results showed that the use of the speed reading method in SD Islam Miftahus Shibyan was inseparable from the steps of the speed reading method and the efforts made by the teacher in teaching and learning activities. The success of using the speed reading method is seen from the student achievement. Of the 67 students studied, 75% showed success.